The effect of genre and tarosi snake and ladders education media on reproductive health knowledge of adolescent in Karangsari Pengasih Village, Kulon Progo, Yogyakarta - Nesti Nur Cahyani; Fatimah Fatimah; Brune Indah Yulitasari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: Reproductive health is a state of physical, mental, and social well-being in all aspects related to the system and its functions and processes. The impact of reproductive health disorders is the occurrence of unwanted pregnancies, transmission of sexually transmitted diseases, and the use of drugs.Objective: This study was to determine the effect of the tarosi genre and educational media on the knowledge of adolescent reproductive health in Karangsari Pengasih Village, Kulon Progo, Yogyakarta.Methods: This type of research is pre-experimental with a one-group pre-posttest design. This research was conducted in Karangsari Pengasih Village, Kulon Progo, with a population of 400 teenagers. The sample of this research is 20 respondents. Bivariate analysis was conducted on the influence of educational media for snakes and ladders Genre and Tarosi on adolescent reproductive health knowledge using Paired t-test for paired samples.Results: This study shows that the level of knowledge of adolescents about reproductive health using Tarosi education media is greater than those using Media Genre, namely the average pre-test score is 11.80 and post-test is 16.40. Moreover, the two media have the same influence on the level of knowledge of reproductive health in adolescents. This can be shown by the results of the significance value of the two media of 0.000˂p 0.05.Conclusion: This study concludes that there is an influence of the tarosi genre and educational media on the knowledge of reproductive health in adolescents in Karangsari Pengasih Village, Kulon Progo Yogyakarta.